The Effect of Agility, Eye Coordination and Concentration on The Skills of Playing Badminton Athletes - Donie Donie; Ronni Yenes; Asep Sujana Wahyuri; Eval Edmizal; Haryadi Halim (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The problem in this research was the lack of agility to do movement, eye-hand coordination between hitting and shuttlecock, and lack of concentration in doing skills playing badminton athletes from West Sumatra. This research aimed to examine and analyze direct and indirect effects of agility, hand eye coordination, and concentration on the badminton playing skills of West Sumatra athletes. The research method used was path analysis approach. The sampling technique was purposive sampling with 21 athletes from a total population of 90 athletes. The data analysis technique was the path analysis approach. The results showed: 1) There was a direct effect of agility on the badminton playing skills of West Sumatra athletes, 2) There was a direct effect of eye-hand coordination on the badminton playing skills of West Sumatra athletes, 3) There was a direct effect of concentration on the skills of playing badminton of West Sumatra athletes, 4) There was a direct effect of agility through concentration on the badminton playing skills of West Sumatra athletes, 5) There was a direct effect of eye-hand coordination through concentration on the skills of playing badminton of West Sumatra athletes.